2017
DOI: 10.3390/coatings7120212
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Growth and Characterization of Indium Tin Oxide Nanocrystal Rods

Abstract: Indium tin oxide (ITO) nanocrystal rods were synthesized in-situ by a vapor-liquid-solid (VLS) method and electron beam evaporation technique. When the electron-beam gun bombarded indium oxide (In 2 O 3 ) and tin oxide (SnO 2 ) mixed sources, indium and tin droplets appeared and acted as catalysts. The nanocrystal rods were in-situ grown on the basis of the metal catalyst point. The nanorods have a single crystal structure. Its structure was confirmed by X-ray diffraction (XRD) and transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The further increase of heating time le only to a minor change in the temperature. The heating characteristics indicated that th temperature saturation values of the ITO/glass substrate system were obtained after 12 s. It should be noted that the presence of SnO 2 and SnO phases in ITO films indicate peaks at 26.5 • and 33.2 • , respectively [27]. The absence of such peaks in the XRD spectrum indicates that only single phase of In 2 O 3 doped with Sn is present in the ITO-5 film.…”
Section: Resultsmentioning
confidence: 89%
“…The further increase of heating time le only to a minor change in the temperature. The heating characteristics indicated that th temperature saturation values of the ITO/glass substrate system were obtained after 12 s. It should be noted that the presence of SnO 2 and SnO phases in ITO films indicate peaks at 26.5 • and 33.2 • , respectively [27]. The absence of such peaks in the XRD spectrum indicates that only single phase of In 2 O 3 doped with Sn is present in the ITO-5 film.…”
Section: Resultsmentioning
confidence: 89%
“…1c), as all the diffraction peaks can be indexed to the standard pattern of In 2 O 3 (PDF #65-3170)-the doping of Sn 4+ in the lattice of In 2 O 3 gives rise to a small shi towards high angles for all the diffraction peaks. 33 The obtained ITO NPs could be easily dispersed in water owing to their hydrophilic surface (see the ESI, Fig. S2 †).…”
Section: Resultsmentioning
confidence: 99%
“…1c ), as all the diffraction peaks can be indexed to the standard pattern of In 2 O 3 (PDF #65-3170)—the doping of Sn 4+ in the lattice of In 2 O 3 gives rise to a small shift towards high angles for all the diffraction peaks. 33 …”
Section: Resultsmentioning
confidence: 99%
“…The most intense reflections in the XRD patterns, marked by a symbol, are attributed to the ITO film [54,55]. Despite the fact that WO 3 is not detected by XRD, the characteristic Raman band associated with the O-W-O stretching modes [53] is still present around 800 cm −1 , as visible in Figure 4 where the micro-Raman spectra of regions of the clean sample surface/surface with agglomerates are respectively shown in the left and right panel.…”
Section: Pure Wo 3 Films: Structural and Morphological Characterizationmentioning
confidence: 99%